Impact of market oriented maize cash crop production on house-hold food security: Bangladesh perspective - Chowdhury, Jannat Adib (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters of Development Studies, 2016.